Power Struggle Over the Mosque: A Study of the Mmi and Kammi Socio-Political Movements - Endrizal, Endrizal; Kahanna, Mutia (Kirana Publisher (KNPub), 2025)
This paper discusses the struggle for power over the mosque that occurred between the Majlis Mujahidin Indonesia (MMI) and the Association of Indonesian Muslim Students (KAMMI) to fight for strategic arenas as political tools to achieve substantive power after the New Order. The author uses a qualitative method with a descriptive analysis approach. Methods of data collection through observation, interviews, and documentation studies with Bukittinggi as the object of research. The findings in this study include the MMI and KAMMI organizations fighting over mosques in the community and campus mosques. Each group will try to win the hearts of the congregation in the mosque to accept their existence. One of them is by following all the activities carried out by the mosque management. They will try to seize the stage by providing tausiyah and religious education to children and youth in the mosque environment. After that, they will replace the old management. The MMI and KAMMI groups make mosques the basis of their struggle in spreading the ideology of organizational struggle. Mastery over the mosque is the first step in the struggle of MMI and KAMMI to achieve organizational goals. The strategy of the MMI and KAMMI groups in achieving their goals is by taking advantage of political opportunities, mobilizing structures, and preparing struggle processes.